Cognitive Enhancement, Prescription Stimulant Use and Health-Related Decision-Making: The Role of Methylphenidate in Healthy Individuals and Subthreshold ADHD - Chmiela, Mateusz; Czesyk, Anna; Krukowski, Bartosz; Słysz, Maciej; Świątko, Ada; Majewski, Michał; Ząbczyńska, Magdalena; Szafraniec, Artur; Janik, Weronika; Korzeniowska, Anna (Journal of Education, Health and Sport, 2026)
The use of methylphenidate beyond clinically diagnosed attention-deficit/hyperactivity disorder (ADHD) has become an important issue in health, educational, and occupational contexts, particularly in relation to cognitive enhancement, performance-related expectations, and the potential misuse of prescription stimulants. ADHD is a neurodevelopmental condition associated with impairments in attention, executive function, and working memory, while subthreshold ADHD symptoms may also be accompanied by measurable cognitive and functional difficulties. The aim of this narrative review was to compare the cognitive effects of methylphenidate in healthy individuals and in individuals with subthreshold ADHD symptoms, with particular attention to whether its action should be interpreted as cognitive enhancement or compensatory improvement. The review was based on a targeted selection of literature identified through PubMed, including randomized controlled trial evidence, meta-analyses, and review studies. Evidence from healthy individuals indicates that methylphenidate produces limited, domain-specific, and inconsistent cognitive effects, with no reliable improvement in attention, working memory, or processing speed. In contrast, individuals with ADHD demonstrate clinically meaningful improvements, particularly in attention and executive function. Subthreshold ADHD may represent an intermediate phenotype, characterized by measurable but less severe impairments, and may therefore show greater responsiveness to methylphenidate than healthy individuals, although direct evidence remains limited. Overall, the findings suggest that the effects of methylphenidate depend on baseline cognitive functioning. These results have implications for health-related decision-making, responsible prescribing, and the evaluation of stimulant use outside strictly diagnosed ADHD populations, where the distinction between treatment, compensation, and enhancement is clinically and socially relevant.